Efficient singlet oxygen generation by triptycene substituted A3B type zinc(II) phthalocyanine photosensitizers. Issue 3 (20th January 2016) - Al-Sohaimi, Bandar R.; Pişkin, Mehmet; Ghanem, Bader S.; Al-Raqa, Shaya Y.; Durmuş, Mahmut
Graphical abstract: Highlights: Synthesis and characterization of triptycene bearing zinc(II) phthalocyanines. Novel A3 B type unsymmetrical zinc(II) phthalocyanines. Photophysical and photochemical properties of these phthalocyanines in toluene. High singlet oxygen generation for photocatalytic applications. Abstract: A3 B type unsymmetrical 8, 11, 15, 18, 22, 25-hexadecyl- 2, 3-(9, 10-dioctyl-6, 7-dimethoxy-2, 3-dioxytriptycene) (11 ) and 8, 11, 15, 18, 22, 25-hexadecyl- 2, 3-(9, 10-diundecyl-6, 7-dimethoxy-2, 3-dioxytriptycene) (12 ) zinc(II) phthalocyanines were synthesized for the first time. Their photophysical and photochemical properties were investigated as solutions in toluene and obtained values were compared with unsubstituted zinc(II) phthalocyanine for determination of substitution effect. Both newly synthesized phthalocyanines showed high singlet oxygen generation making them good candidates as photosensitizers for photocatalytic reactions.